2016
DOI: 10.1007/112_2015_5004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Response to Oxidative Stress Induced by Mitochondrial Dysfunction

Abstract: The heart works without resting, requiring enormous amounts of energy to continuously pump blood throughout the body. Because of its considerable energy requirements, the heart is vulnerable to oxidative stress caused by the generation of endogenous reactive oxygen species (ROS). Therefore, the heart has effective regulatory and adaptive mechanisms to protect against oxidative stress. Inherited or acquired mitochondrial respiratory chain dysfunction disrupts energy metabolism and causes excessive ROS productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 179 publications
0
15
0
1
Order By: Relevance
“…It has been identified as a potential new "gold standard" for early clinical diagnosis and grading regarding to its noninvasiveness. In our previous study, the 18 F-FDG PET/CT had been performed to explore the adverse effects of PM 2.5 on pulmonary system. 64 And the assessment method of 18 F-FDG PET/CT was recommended to explore the melatonin-mediated protective role in future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been identified as a potential new "gold standard" for early clinical diagnosis and grading regarding to its noninvasiveness. In our previous study, the 18 F-FDG PET/CT had been performed to explore the adverse effects of PM 2.5 on pulmonary system. 64 And the assessment method of 18 F-FDG PET/CT was recommended to explore the melatonin-mediated protective role in future.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Mitochondria are essential organelles to maintain the fundamental physiology in heart tissues through energy metabolism and catabolic oxidative reactions. 17,18 The processes of mitochondrial metabolism are dependent on the two NAD+-dependent enzyme families, sirtuins (SIRTs) and poly (ADP-ribose) polymerases (PARPs). 19,20 The SIRTs family (SIRT1-SIRT7) could affect their target proteins activities by deacetylation which transfers an acetyl group from their target proteins to ADP-ribose moiety of NAD+ to form 2-O-acetyl-ADP-ribose and NAM.…”
mentioning
confidence: 99%
“…A previous study demonstrated that cardiac mitochondria are vulnerable to oxidative stress (Kim et al, 2016 ). In order to evaluate the mitochondrial functions of HT-22 cells in response to H 2 O 2 , mitochondrial membrane potential was detected by JC-1 staining.…”
Section: Resultsmentioning
confidence: 99%
“…22 Similarly, extrapolation of our findings to explain the controversial 23,24 better CVD prognosis of subjects with preserved insulin sensitivity is not feasible, but if we speculate that the adaptation of energy metabolism and lipid disposal detected at the whole body system was taking place also at the level of the heart, this event could be an effective mechanism to protect against mitochondrial respiratory chain dysfunction and in turn excessive ROS production and oxidative stress. 25 Following this line of thinking a recent work performed in a population of Indonesian patients with T2DM reported that body composition and overall estimated REE using BIA were strongly associated with and contributed considerably to the presence and severity of diabetic retinopathy independent of other systemic factors including diabetes duration, blood pressure, diabetes medication, and other diabetes complications. 26 Limitations of the present work are the crosssectional and retrospective nature of the analysis, the assessment of body composition using BIA methodology and the lack of knowledge for food preference.…”
Section: Discussionmentioning
confidence: 98%